2017
DOI: 10.1186/s12861-017-0151-3
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Ciona intestinalis AOX causes male reproductive defects in Drosophila melanogaster

Abstract: BackgroundMitochondrial alternative respiratory-chain enzymes are phylogenetically widespread, and buffer stresses affecting oxidative phosphorylation in species that possess them. However, they have been lost in the evolutionary lineages leading to vertebrates and arthropods, raising the question as to what survival or reproductive disadvantages they confer. Recent interest in using them in therapy lends a biomedical dimension to this question.MethodsHere, we examined the impact of the expression of Ciona int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 42 publications
(58 reference statements)
0
15
0
Order By: Relevance
“…However, it is unclear how the AOX-mediated changes in the QH 2 /Q ratio can impact metabolism and subsequently, ROS production at other mitochondrial sites. Recently, AOX expression was shown to decrease male fertility in Drosophila melanogaster [67]. While the role of ROS in mediating fertility is unclear, it demonstrates that AOX can influence physiologic processes.…”
Section: Detecting and Modulating Ret Ros Generationmentioning
confidence: 99%
“…However, it is unclear how the AOX-mediated changes in the QH 2 /Q ratio can impact metabolism and subsequently, ROS production at other mitochondrial sites. Recently, AOX expression was shown to decrease male fertility in Drosophila melanogaster [67]. While the role of ROS in mediating fertility is unclear, it demonstrates that AOX can influence physiologic processes.…”
Section: Detecting and Modulating Ret Ros Generationmentioning
confidence: 99%
“…Sperm expressing AOX, which bypasses a major site of mtROS formation in the electron transport chain, complex III [28], would therefore be expected to show lower ROS production. Given our results, it seems likely that, while AOX is expressed in the testes and seminal vesicles of AOX males [29], it is not expressed in the germline itself. Although the daGal4 driver is supposedly ubiquitously expressed, it is not unusual for "ubiquitous" drivers to show no expression in germ cells [30].…”
Section: Discussionmentioning
confidence: 66%
“…Considering that the genes encoding any alternative enzyme have been lost independently from the evolutionary lines that led to the arthropods and vertebrates, it is plausible that these enzymes might also impact these animals’ fitness negatively. We have recently investigated male reproductive success in AOX‐expressing flies as an important component of fitness, and showed that AOX can cause a significant decrease in mature sperm production, due to an abnormal accumulation of these cells in the testes (Saari et al, ). These males reproduce normally under non‐competitive conditions, but are ultimately unable to succeed in sperm competition assays against wild‐type males, the most likely reproductive condition present in nature for Drosophila .…”
Section: Potential Negative Impacts For Animal Physiology and Reprodumentioning
confidence: 99%